Politik Hukum dalam Amandemen Pasal 29 UUD 1945 Telaah terhadap Upaya Penerapan Syari’ah Islam di Indonesia - Nursalim, Muh (Unisia, 2012)
To describe the struggle of moslem community regarding Islamic Shariah enformcement in Indonesia legal-formally in parliament. This should be started from describing the forming of the constitution of the state philosophically and the theory of the changing of the constitution. These needs to be done because of at New Order regime era has ever sacralized the consti- tution 1945 , and the changing of the Constitution 1945 is equal to the end of the state. In this context, because of the difficulty to amend article 29 of the Constitution 1945 about religion, it implies to modify the law, for instance the implementation of Shari’ah based on the Constitu- tion 1945. In other word, to interpret article 29 of the Constitution 1945 by paying attention to the historisity of articles when they are constructed. Based on this way, shariah implementation in Indonesia could be done without amending article 29 of the Constitution 1945. Kaywords: Amendments, Politic, Shari’ah Enforcement